Does Intraoperative Ketorolac Increase Bleeding in Oculoplastic Surgery?. Issue 4 (July 2020) - Chang, Minwook; Gould, Adam; Gur, Zvi; Buhbut, Ortal; Hosalkar, Hetal; Liu, Catherine Y.; Korn, Bobby S.; Kikkawa, Don O.
Abstract : Purpose: To report adverse hemorrhagic outcomes in patients who received intravenous (IV) ketorolac during oculofacial plastic surgical procedures. Methods: The medical records of 111 consecutive patients who underwent lacrimal or orbital surgery, between the years 2016 and 2018, performed by a single surgeon under general anesthesia were retrospectively reviewed. Patients were excluded if they had history of a bleeding coagulopathy, anticoagulant use prior to surgery, or insufficient follow up. Patients were divided into 2 groups based on whether they received intravenous ketorolac. The primary outcome measure was the occurrence of a major postoperative bleeding event, and the secondary outcome measures were the evaluation of postoperative ecchymosis graded at 1 week after surgery and the incidence of persistent ecchymosis beyond 4 weeks. Results: A total of 111 patients were analyzed further, including 31 patients who received intraoperative IV ketorolac and 80 control patients who did not. The demographic characteristics between the 2 groups were similar. No major bleeding events occurred in either group. And there was no statistically significant difference between the 2 groups in terms of ecchymosis grade and the incidence of development of persistent ecchymosis. Comparing the subgroups of lacrimal and orbital cases, there was also no significance difference between these groups. Conclusions: This study suggests that intraoperative ketorolac use does not increase the risk of postoperative bleeding complications in oculofacial procedures. This alternative to opioids may assist with pain control and lessen the narcotic burden. Abstract : Intraoperative ketorolac use does not increase the risk of major bleeding events during and post oculofacial plastic procedures.